التنظيم القانوني لأسهم الخزينة وفقاً للقانون السوري - مرهج عمار يوسف (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يتميز مفهوم أسهم الخزينة وتنظيمها القانوني بالغموض المحيط به، ذلك أنهُ يطرحُ عدداً من التساؤلات القانونية المشروعة، سواء لجهة إمكانية اعتبار الشركة مساهمةً بذاتها في حال احتفاظها بجزء من أسهمها من عدمه، أم لجهة خصائص هذه الأسهم ومدى التشابه الحاصل بينها وبين سندات وأسهم أخرى، وأخيراً ما يتعلق منها بمصير هذه الأسهم وجوداً أو انعداماً وآثارها على هذا الصعيد، الأمر الذي يجعل من دراسة تنظيمها القانوني,ثم البحث في مفهومها ومصيرها بيعاً أو إلغاءً في ظل التشريع السوري ضرورةً ملحة، بحسبانها قد تسهم في إزالة ما يعتريها من غموض لدى الشركات أو المستثمرين في سوق دمشق للأوراق المالية، و التخفيف من إمكانية تحولها إلى أداة احتيالية. The concept of treasury shares and its legal regulation characterized by the mystery surrounding it, because of it raises a number of legal questions legitimate, both in terms of the possibility of the company considered the contribution of it salve or not, or in terms of the characteristics of these stocks and the extent of similarity quotient between bonds and other stocks, Finally, with regard to the fate of these shares and the presence or a lack and its effects on this level, which made the study of the legal regulation through research in the concept and doomed to a sale or cancellation under Syrian legislation is an urgent need, that those standards may contribute to the removal of what undergo the ambiguity of corporate or investors in the Damascus Securities Exchange, thereby reducing the possibility of its transformation into a fraudulent tool.